Common disputes in oil and gas industry and the ADR process - Wan Zahari, Wan Mohd Zulhafiz; Mohamed, Nurah Sabahiah (Ahmad Ibrahim Kulliyyah of Laws (AIKOL), International Islamic University Malaysia, 2017)
The offshore petroleum projects involve broad of variety contracts entered by multiple parties to operate complex, expensive and high-risk activities. In this regards, the oil and gas sector has its own unique features in doing business. For instance, the oil and gas contracts re-allocate risk which may seem vivid to outsiders but seems perfectly reasonable for the industry. It also has its own outlooks on dispute resolution. The parties in the oil and gas industry prefer to opt for alternative dispute resolution (ADR) processes rather than litigation. ADR refers to all means of dispute settlement other than litigation such as negotiation, mediation, adjudication, and arbitration. This paper also discusses common disputes in the oil and gas industry such as the litigation arose from the Deepwater Horizon case (it also known as Macondo case) which happened in the Gulf of Mexico in 2010. Subsequently, this paper examines the ADR processes in the oil and gas industry. On this point, this paper argues that, due to the complexity and technicalities of operations in the oil and gas sector, there is a need to set up a particular arbitration centre to handle and resolve the disputes. In doing so, a special legal framework is needed to establish a special centre for oil and gas as a roadmap for the industry key players in resolving their dispute. The methodology employed in this research will be a comparative analysis which will be carried out in a descriptive, analytic and prescriptive manner.